(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Context: Using the co-crystallization approach, the current work aimed to increase the solubility of piroxicam (a BCS class II medication) and construct buccal films of specific co-crystals for better drug therapeutic usage. Solvent evaporation was used to generate co-crystals of medication with different co-formers (molar ratio 1:1), which were then evaluated for % drug content and water solubility. FTIR, DSC, and XRD all corroborated the co-crystal formation. Buccal films containing piroxicam co-crystals were made, and their in vitro and ex vivo drug penetration was assessed. A histological analysis was used to ascertain the formulation’s safety. Findings: It has been shown that the co-crystals made with various co-formers have the ability to increase the drug’s solubility. Piroxicam-sucralose co-crystals have shown six times more solubility than the parent medication. The FTIR measurement revealed a change in the piroxicam’s distinctive peaks. An additional exothermic peak and a change in the typical endothermic peak were revealed by DSC analysis. There were variations in the 2θ values of the strong peaks in the powder x-ray diffraction pattern. Co-crystal formation was thus verified. Characteristics of buccal films were determined to be within acceptable bounds. Formulation F2 had the maximum in vitro drug release after 8 hours, or 94.557%, but formulation F6 demonstrated the highest mucoadhesive strength (5617 ± 636 dynes /cm2). It was discovered that 84.74% of F2 was drug-permeable ex vivo. The histopathological analysis showed that the buccal mucosal tissue was intact and had not been damaged. In conclusion, piroxicam-suralose co-crystals-based mucoadhesive films may represent a more effective formulation strategy than traditional tablets, offering greater solubility, safety, and therapeutic effectiveness.